2001
DOI: 10.1002/ijc.1321
|View full text |Cite
|
Sign up to set email alerts
|

Thiolutin, an inhibitor of HUVEC adhesion to vitronectin, reduces paxillin in HUVECs and suppresses tumor cell-induced angiogenesis

Abstract: Recent studies have shown that integrin ␣v␤3, a receptor for vitronectin, plays an important role in tumor-induced angiogenesis and tumor growth and that antagonists of ␣v␤3 inhibit angiogenic processes including endothelial cell adhesion and migration. On the other hand, most inhibitors of integrin ␣v␤3 are peptide antagonists that include the ArgGly-Asp (RGD) motif. We therefore reasoned that non-peptide inhibitors of endothelial cell adhesion to vitronectin might be useful for inhibition of tumor angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…Consistent with the previously reported effect of thiolutin on endothelial cell adhesion on vitronectin (Minamiguchi et al 2001), we found that ≥0.4 μM thiolutin was sufficient to rapidly and completely disrupt adhesion of attached HUVEC monolayers (Fig. 3a).…”
Section: The Effect Of Thiolutin On Huvec Adhesion Is Reversiblesupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the previously reported effect of thiolutin on endothelial cell adhesion on vitronectin (Minamiguchi et al 2001), we found that ≥0.4 μM thiolutin was sufficient to rapidly and completely disrupt adhesion of attached HUVEC monolayers (Fig. 3a).…”
Section: The Effect Of Thiolutin On Huvec Adhesion Is Reversiblesupporting
confidence: 92%
“…1a) and its effects on endothelial cells in vitro (Minamiguchi et al 2001;Dai et al 2008), we investigated the effect of thiolutin on vertebrate development using the transparent zebrafish model system. In addition to obtaining toxicology data, the effect of thiolutin on developmental angiogenesis was assessed using the transgenic zebrafish line Tg(fli1:EGFP) y1 , which carries a 15-kb promoter of friend leukemia integration-1 transcription factor (fli1) that drives green fluorescent protein (GFP) expression in the developing vasculature (Lawson and Weinstein 2002).…”
Section: Thiolutin Disrupts Zebrafish Embryonic Development and Distumentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14] Dithiolopyrrolones have also been reported to have anticancer activity, [15][16][17] and shown potent membrane stabilization and platelet anti-aggregate activities. 18 We first reported that ZL-004 ( Figure 1) exhibited antileukopenia activity.…”
Section: Introductionmentioning
confidence: 99%